Pengaruh Kualitas Pelayanan dan Kepercayaan Pelanggan terhadap Minat Membeli Ulang pada Restoran Ayam Square Signature Cabang Epicentrum Mall di Kota Mataram - Meuthia Nandika Syahbudin; Hilmiati Hilmiati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the influence of Service Quality and Customer Trust on Repurchase Intention at Ayam Square Signature Restaurant in Mataram City. The research method used was a quantitative approach with a survey technique. The sample consisted of 100 respondents selected using purposive sampling with the criteria of having purchased at least once within the last six months. Data were collected directly through questionnaires using Google Forms. Data analysis was conducted using multiple linear regression, t-test, and F-test with the assistance of SPSS version 29. The results showed that Service Quality had a positive and significant effect on Repurchase Intention. This was proven by the t-value 9.493 > t-table value of 1.985, and a significance level of 0.001< 0.05. In addition, Customer Trust also had a positive and significant effect on Repurchase Intention, with a t-value 9.117 > t-table value 1.985 and a significance level of 0.001<0.05. Based on the simultaneous test results, the significance value was 0.001<0.05 and the F-value was 85.161 > F-table value of 3.090. This indicates that Service Quality and Customer Trust simultaneously had a significant effect on Repurchase Intention at Ayam Square Signature Restaurant in Mataram City.